Murine cytomegalovirus-associated pneumonitis in the lungs free of the virus. - Tanaka, K (1994)
At 4 wk after intraperitoneal inoculation of murine cytomegalovirus (MCMV) in adult BALB/c mice, MCMV remained detectable only in the salivary glands. When T cells of these mice were activated by a single injection of anti-CD3 epsilon monoclonal antibody, mice died of interstitial pneumonitis at 24-48 h after injection, accompanied by elevation of serum levels of TNF-alpha and IFN-gamma. However, MCMV remained undetectable in the lungs during the period. Simultaneous injection of cyclosporin A reduced such effects of anti-CD3. In conclusion, although the presence of MCMV in the host may be required, MCMV-associated pneumonitis is not mediated by virus in the lung but probably by the cytokines released from T cells, of which responsiveness to stimulation via CD3 molecule has been presumably modified by MCMV infection.